(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Pigeon pea is a perennial legume with a good nutritional value. Unfortunately, it is also a substrate for fungi contamination. Then, a qualitative semi-structured survey was carried out in the main production areas of pigeon pea in southern Benin. This survey was coupled with samples collection. A total of 60 samples of pigeon pea were collected and analyzed for associated fungal microflora by using a taxonomic schemes primarily based on morphological characters of mycelium and conidia. Obtained results indicated a low technological valorization of pigeon pea seeds in southern Benin and their used only in direct consumption after cooking. Microbiological analyses revealed the high contamination of pigeon pea seeds by fungi, with the most occurrence of Aspergillus (71.42%), followed by Fusarium (26.19%). Fungal species such as Aspergillus ochraceus, A. parasiticus, A. flavus and Fusarium oxysporum were also detected in analyzed samples. Taking into account the toxicity of the secondary metabolites produced by these fungi, mycological hazards are discussed and important methods for the control of mycotoxin-contamination are further provided. More attention should be paid to the mycological quality of this legume, in order to protect the consumers’ health.